DETERMINATION OF THE LINE OF INTERSECTION OF SURFACES - Yuldashov Batiyor Botirovich; Jurayev Fazliddin; Turdibayeva Mavluda Ravshan kizi; Isayev Sunnatullo Dilshodovich (Web of Journals Publishing, 2024)
Determining the intersection of surfaces is a fundamental concept in mathematics and physics, especially in the study of three-dimensional geometry. When two surfaces intersect, they form a line where the points on both surfaces coincide. This line represents the common boundary between two surfaces and provides important information about their relationship and properties.
Keywords: surface, intersection line, engineering graphics, point, geometry.